2021
DOI: 10.3390/ijms22116166
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA Epigenetics

Abstract: Long noncoding RNAs exceeding a length of 200 nucleotides play an important role in ensuring cell functions and proper organism development by interacting with cellular compounds such as miRNA, mRNA, DNA and proteins. However, there is an additional level of lncRNA regulation, called lncRNA epigenetics, in gene expression control. In this review, we describe the most common modified nucleosides found in lncRNA, 6-methyladenosine, 5-methylcytidine, pseudouridine and inosine. The biosynthetic pathways of these n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 189 publications
(293 reference statements)
0
19
0
Order By: Relevance
“…This is achieved by ncRNAs’ ability to interact with various biological molecules ( Figure 3 ) within different cells and tissues. Among these ncRNAs with regulatory functions, this review particularly focuses on miRNAs and lncRNAs, which have attracted great interest given their roles in various biological functions [ 51 , 65 , 66 , 67 ].…”
Section: Ncrnas With Regulatory Functionsmentioning
confidence: 99%
“…This is achieved by ncRNAs’ ability to interact with various biological molecules ( Figure 3 ) within different cells and tissues. Among these ncRNAs with regulatory functions, this review particularly focuses on miRNAs and lncRNAs, which have attracted great interest given their roles in various biological functions [ 51 , 65 , 66 , 67 ].…”
Section: Ncrnas With Regulatory Functionsmentioning
confidence: 99%
“…Long non-coding RNA (lncRNA), a kind of non-coding RNA recognized recently with a length of more than 200 bp, has been reported to regulate a huge amount of biological processes and to be involved in the pathogenesis of most diseases via its interaction with cellular compounds such as miRNA, mRNA, DNA, and proteins (9)(10)(11)(12)(13). Besides, lncRNA has been also observed to be deeply involved in the development, progression, and treatment response of hematological malignancies (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data have shown that lncRNAs play a key role in the pathogenesis of cardiac remodeling and heart failure ( 11 ). Many mature lncRNAs are modified after transcription, and numerous types of biochemical modifications were found in lncRNAs ( 12 ). The relationship between lncRNAs and m6A modifications still remain largely unknown, provides a fresh viewpoint for exploring the possible regulatory mechanism and suggests that m6A modification and lncRNAs interplay might be significant treatment targets for various diseases ( 13 ).…”
Section: Introductionmentioning
confidence: 99%